2011
DOI: 10.3747/co.v18i4.913
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trends in the Treatment of Triple-Negative Breast Cancer in Canada: A Survey

Abstract: age at onset, large mean tumor size, high grade and higher incidence of node positivity at presentation compared to what is expected based on tumor size. TN status remains an independent risk factor for distant relapse and survival, with a rapid rise in distant relapse in the first three years after diagnosis 2,7 . additionally, patients with TN breast tumors have an increased propensity for lung and brain metastases, making these tumors especially challenging to treat.Molecular classification of breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…An updated U.S. Oncology trial report has demonstrated benefit in disease-free and overall survival for 4 cycles of docetaxel-cyclophosphamide (tc) chemotherapy over doxorubicin-cyclophosphamide chemotherapy and has also reported acceptable toxicity, with a fn rate of 5% 4 . The tc regimen has become very popular in Ontario, particularly in older age groups who are at increased risk of cardiotoxicity with anthracyclines and in patients eligible for trastuzumab 5 .…”
Section: Introductionmentioning
confidence: 99%
“…An updated U.S. Oncology trial report has demonstrated benefit in disease-free and overall survival for 4 cycles of docetaxel-cyclophosphamide (tc) chemotherapy over doxorubicin-cyclophosphamide chemotherapy and has also reported acceptable toxicity, with a fn rate of 5% 4 . The tc regimen has become very popular in Ontario, particularly in older age groups who are at increased risk of cardiotoxicity with anthracyclines and in patients eligible for trastuzumab 5 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, after the treatment, the monitoring of the disease should be evaluated by imaging techniques like MRI which is the most sensitive imaging method for measuring TNBC neoadjuvant response-treatment [105]. Precision medicine strategies identify strategic biomarkers in each oncological patient, providing a more effective and selective chemotherapy regimen [106]. Within the margins of personalized medicine, medical research suggests that for TNBC treatment, one of the most useful molecular targets is EGFR since it is positively expressed (around 60%) in TNBC [107].…”
Section: Neoadjuvant Therapymentioning
confidence: 99%
“…Mutations in the KRAS gene occur in multiple tumour types including colorectal carcinoma, non-small cell lung cancer and pancreatic carcinoma. Some mutations in the KRAS gene (approximately 40% of colorectal carcinomas) and the NRAS gene (approximately 1%–6%) are associated with poor prognosis and a lack of response to anti-EGFR antibody therapy such as cetuximab and panitumumab [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Colorectal Carcinomamentioning
confidence: 99%